Assessing diagnostic performance of plasma biomarkers in Alzheimer’s disease versus cognitively unimpaired individuals: P-tau217 emerges as the optimal marker in Chinese cohorts - Wang, Shinan; Liu, Dequan; Li, Haiyan; Jia, Xiaodong; Zhou, Hailan; Yu, Wenying; Li, Tong; Pan, Liping; Chen, Baorong; Wang, Yujia; Zhan, Nan; Song, Yijun; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionThe Simoa platform is recognized as a highly sensitive tool for detecting blood-based biomarkers of Alzheimer’s disease (AD). It is extensively utilized in the diagnosis and identification of AD, with accuracy emerging as a pivotal metric for assessing assay performance, gradually gaining acceptance and application. The primary objective of this study was to assess the diagnostic efficacy of multiple biomarkers in AD using the Simoa platform. The ultimate goal was to identify the optimal diagnostic biomarkers and further investigate their practical application value in the Chinese population.MethodsThe study comprised two cohorts: cohort I consisted of 151 healthy controls and 90 AD patients, while cohort II was sourced from a Chinese population cohort, encompassing 123 healthy controls and 126 AD patients, utilizing publicly available data. All patients underwent plasma biomarker concentration measurements using the Simoa platform. The specificity, sensitivity, and accuracy of these biomarkers for AD diagnosis were compared to evaluate their diagnostic efficacy.ResultsThe findings revealed that plasma P-tau217 exhibited excellent performance in differentiating AD from healthy controls, with a sensitivity of 95.0%, specificity of 96.0%, and accuracy of 95.7% for AD diagnosis. Conversely, other indicators, including Aβ42, Aβ42/40, T-tau/Aβ42, P-tau217/Aβ42 and P-tau181, demonstrated some diagnostic efficacy but fell short of meeting the diagnostic criteria.DiscussionP-tau217 stands out as a highly effective biomarker for distinguishing AD from CUC, exhibiting extensive clinical application potential in the Chinese population. It presents a promising array of clinical prospects for the Chinese population.